Periodontal Status and Risk Factors among Adults of Sebha City (Libya) - Syed Wali Peeran; A. J. A. Ranjith Singh; G. Alagamuthu; Syed Ali Peeran; P. G. Naveen Kumar (International Journal of Dentistry)
The present study was aimed at assessing the periodontal status and risk factors like age, gender, tooth brushing habit, and smoking among the adult population of Sebha city, Libya. 452 adults, aged 35–54 years, comprised the study sample. 266 (58.84%) were females and 186 (41.15%) were males. Data was collected by interview and clinical examination using CPI of CPITN index. Chi-square test and ANOVA were used for statistical analysis at 5% level of significance. Results indicate that 76.32% used toothbrush and paste; 8.84% were current smokers and were all males. Majority, 52.65% were, detected with shallow pockets followed by 30.08% with calculus, 12.17% had deep pockets, 3.31% had bleeding, and only 1.33% were healthy. Age, gender, current smoking status and frequency of tooth brushing showed statistically significant difference with CPI codes. Health professionals can utilize this data to identify individuals at risk and to target population level interventions.